PENGARUH PROSES REKRUTMEN DAN SELEKSI TERHADAP KUALITAS KERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH DKI JAKARTA - Joko Budiraharjo; Meirna Milisani; Yulia Marosani (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2022)
The objectives of this study are: 1) To find out whether there is an effect of the recruitment process on the quality of work at the DKI Jakarta Regional Development Planning Agency 2) To find out whether there is an effect of selection on the quality of work at the DKI Jakarta Regional Development Planning Agency. 3) To find out whetherthere is an effect of the joint recruitment and selection process on the quality of work at the DKI Jakarta Regional Development Planning Agency.In this study the author uses quantitative research, because the data obtained will be in the form of numbers. The population in this study were 40 employees of the DKI Jakarta Regional Development Planning Agency. The sampling technique used in this research is saturated sampling. By using the saturated sampling technique, a sample of 40 employees of the DKI Jakarta Regional Development Planning Agency was taken as respondents in this study.The results showed that: 1) There was an influence of the Recruitment Process variable (X1) of 5,135 while the ttable value for n = 60 was 2,000. So 5,135 2,000, it can be concluded that partially the recruitment process variable (X1) has an effect on the quality of employee work (Y). 2) There is an effect of the Selection variable (X2) of 6.357 while the ttable value for n = 60 is 2,000. So 6,357 2,000, it can be concluded that partially the Selection variable (X2) has an effect on the Quality of Employee Work (Y). 3) There is an effect of the Recruitment and Selection Process on the Quality of Employee Work, as evidenced by the R Square value of 0.611. This shows that 61.1% of the Recruitment and Selection Process has a positive effect on the Quality of Employee Work while the remaining 38.9% has an effect on other factors not examined in this study.Keywords: Recruitment Process, Selection and Quality of Employee Work